2015
DOI: 10.3906/sag-1401-111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 75 pandemic H1N1 influenza patientsfrom Turkey; risk factors for fatality

Abstract: Background/aim: The 2009 influenza A (H 1 N 1 ) pandemic caused mild to severe illnesses and led to death in some cases. In this study, we aimed to evaluate the relationship between the serum D-dimer levels, CURB-65 scores, and the severity of pneumonia among patients with H 1 N 1 infections.Materials and methods: Sixty-eight patients who had probable H 1 N 1 infections were evaluated by clinical, radiological, and laboratory methods. The H 1 N 1 strain was specified by reverse transcription-polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“… 40 Two other studies of patients with probable IAV H1N1 infection found that D -dimer predicted disease progression. 77 , 78 Elevated plasma levels of D -dimer have also been reported in SARS-CoV–infected patients. 79 D -dimer has attracted attention as a prognostic marker in COVID-19 patients.…”
Section: Pandemic Respiratory Viruses Activate the Coagulation Systemmentioning
confidence: 99%
“… 40 Two other studies of patients with probable IAV H1N1 infection found that D -dimer predicted disease progression. 77 , 78 Elevated plasma levels of D -dimer have also been reported in SARS-CoV–infected patients. 79 D -dimer has attracted attention as a prognostic marker in COVID-19 patients.…”
Section: Pandemic Respiratory Viruses Activate the Coagulation Systemmentioning
confidence: 99%
“…Albumin (mg ml IAV infections are prothrombotic in humans, which can result in an increase in Fg at the site of infection [15,[43][44][45]. Because Fg is an important ligand of the M protein, it was of interest to measure the abundance of Fg in our murine model of IAV-GAS superinfection.…”
Section: Iav-gas Superinfection Increased the Abundance Of Fg In The mentioning
confidence: 99%
“…Eighteen (53%) items focused on 2009 and 2010 [26,29,35,37,38,[40][41][42][43][44][45][46][47][48][49][50]. Only 4 (12%) collected patient data earlier than 2009 [24,34,51,52].…”
Section: Study Search Results and Selectionmentioning
confidence: 99%